Luminescent Dansyl-Calix[5]arene for the Recognition of Biogenic Amines - Testa, Caterina; Gangemi, Chiara M.A.; Sfrazzetto, Giuseppe T.; Ricceri, Martina; Giuffrida, Alessandro; Greco, Valentina; Cancelliere, Ambra Maria; Puntoriero, Fausto; Pappalardo, Andrea (Current Organic Chemistry, 2024)
A luminescent calix[5]arene with a covalently linked dansyl chromophore substituent has been successfully used, both in solution and in the gas phase (ESI-MS), for the recognition of biogenic amines that contain linear alkylammonium structural unit. Binding constant values, determined by fluorescence spectroscopy, revealed a greater affinity for cadaverine, spermidine, and L-lysine, in which the terminal ammonium group allows for additional stabilizing interactions with the dansyl moiety.
Keywords: biogenic amines